Is it too much or not enough to click? Examining how and when the vertical visual perspective affects consumers' click-through intention - Wu, Heng; He, Wenjun; Li, Xiaodan; Ye, Hui (International journal of hospitality management, 2024)
In addition to explicit informational cues, hotel managers can persuade consumers using subtle visual cues that convey symbolic meanings. This study examines the interaction effects of the vertical visual perspective (low-level vs. eye-level) in hotel cover photos and hotel type (higher-end vs. lower-end) on consumers’ click-through intention on the search results page of OTAs, the underlying mechanism, and the moderating effect of consumers’ power distance beliefs (PDB) based on conceptual metaphor theory. Using a mixed-methods approach, this study tested the proposed model through three scenario-based between-subject experiments and verified it with a large-scale experiment. The findings reveal a metaphoric compensatory effect: a low-level perspective is effective in increasing click-through intention for lower-end hotels, while an eye-level perspective is effective for higher-end hotels, with positive emotions mediating this effect. Notably, this effect holds for consumers with high PDB but not for those with low PDB. This study has theoretical and practical implications. •Eye-level (vs. Low-level) cover photos increase click-through intention for higher-end (vs. lower-end) hotels.•Power distance belief moderates the interaction effect of visual perspectives and hotel types.•Positive emotion plays a mediating role as the underlying mechanism.